Single visit endodontic treatment and zirconia crown restoration for functional and esthetic rehabilitation - Galih Sampoerno; Ratih Mutiara Sani; Hasna Shabrina; Jasmina Putri Azizia; Ramdhan Hanif Nahada; Radixtio Auzan Fepiosandi; Nanik Zubaidah; Widya Saraswati (Conservative Dentistry Journal, 2025)
Background: Endodontic treatment followed by full-coverage restoration represents the standard of care for structurally compromised posterior teeth. The integration of contemporary endodontic techniques with high-strength esthetic materials, such as zirconia crowns, facilitates comprehensive functional and esthetic rehabilitation in a single treatment sequence, particularly for younger patients with high esthetic expectations. Purpose: To present a successful case of single-visit endodontic treatment followed by fiber post placement and zirconia crown restoration on a mandibular molar in a young female, resulting in favorable functional and esthetic outcomes. Case: A 20-year-old female presented with persistent spontaneous pain in the lower left posterior region for one week, following two years of untreated dental caries. Initial management was conducted at a primary health center with pain control. Clinical and radiographic examination revealed a deep Class II caries lesion with pulp exposure on tooth 36 and a positive percussion response, indicative of irreversible pulpitis. Case Management: Tooth 36 underwent single-visit root canal therapy using a crown-down pressureless technique and single-cone obturation. This was followed by fiber post placement for coronal reinforcement and definitive restoration with a zirconia crown. At the one-week follow-up after crown cementation, the tooth exhibited excellent functional performance, stable periapical healing, intact crown margins, and high patient satisfaction with the esthetic result. Conclusion: This case demonstrates the clinical efficiency and long-term esthetic advantages of combining single-visit endodontic therapy with zirconia crown restoration in young adult patients.